Graceful gait: virtual ballet classes improve mobility and reduce falls more than wellness classes for older women - Harrison, Elinor C.; Haussler, Allison M.; Tueth, Lauren E.; Baudendistel, Sidney T.; Earhart, Gammon M. (Frontiers in Aging Neuroscience, 2024)
Introduction: Dance is an effective and motivating form of exercise for older women, but few studies have quantified the benefits of virtual dance classes nor, specifically, ballet. This study tested the effectiveness of virtual ballet compared to virtual wellness classes, with the goal of reaching underserved populations. It is among the first to explore the effects of virtual classical ballet on functional gait mobility, balance, and quality of life measures in older women. Methods: Older women were recruited in two waves and randomized to two groups: a ballet class modified for older adults and a wellness-based control class. Both groups received 12 weeks of online classes, meeting twice per week for 45-minute sessions. Classes were taught by a local company that offers community-based ballet classes. The same instructor led both the ballet and the wellness classes. Pre-and post-intervention assessments include gait and balance testing using wearable inertial sensors and self-report outcomes including quality of life and mood questionnaires.Results: Forty-four older women completed the study: Ballet group (n=21, 67.81±7.3 years); Wellness group (n=23, 69.96±6.7 years). Pre-to post-intervention, both groups increased velocity on the two-minute walk test (F1,42=25.36, p<.001) and improved their time on the Timed Up and Go (F1,42=4.744, p=.035). Both groups improved balance on the Mini-BESTest (F1,42=38.154, p<.001), increased their scores on the Activities-Specific Balance Confidence Scale(F1,42)=10.688, p<.001), and increased quality of life via the Short Form Health Survey (F1,42=7.663, p=.008). The ballet group improved gait variability in the backward direction (F1,42=14.577, p<.001) and reduced fall rate more than the wellness group (χ 2 (1)=5.096, p=.024).Discussion: Both virtual ballet and wellness classes improve select measures of gait, balance, and quality of life. The benefits seen in both groups highlight the importance of considering social interaction as a key component when developing future interventions to target mobility in older women.